De contextos do fazer pedagógico : entre formação continuada e tecnologias da informação e comunicação - Frozi, Valtrícia Lucelita (2012)
This study is the result of research by master´s degree in Education UFMT. It aims to observe the relationships between the teachers of Basic Education from Fernando Leite de Campos School with educational Technologies and the influence of these on their pedagogical teaching from the presupposition of continuing education on blended mode offered by the MEC by E-PROINFO platform. Consisted locus of the research of State School Fernando Leite de Campos and the subjects were the teachers that in 2010 completed the Course “ Developing Projects – PITEC” offered by the MEC and made possible for CEFAPRO (Center for Professional Training and Upgrading of Basic Education) form Cuiaba by E-PROINFO platform. This study presents a qualitative approach and the methodology is an exploratory descriptive. The methodology that guides the research is based on the Theoretical contributions of Denzin and Lincoln (2006) and Andrew & Lüdke (1986). As data collection instruments were used questionnaires with open and closed questions, and these questionnaires were answered by the subjects (teachers) and observations were conducted in the school environment made by the researcher. The results showed that although timid, there are interesting attempts about the use of TIC (Information and Communication Technologies) at school. It is observed that there is still much to be gained for the integrated use of TIC promotes learning and they don´t be used just as extension of the textbook. Are evident the fragility of the School about the deployment of computer labs and other spaces; It also realizes that computer labs and this spaces have not yet been understood and articulated with the learning objectives. The continuing education may contribute to new contexts originate in the teaching practice in relation to the integrated use of TIC.